Longitudinal association of urbanization and risk of myocardial infarction in China: an analysis from the China Health and Nutrition Survey - Bin Dong; Qun Xiong; Jia Li; Ruicong Xue; Jiangui He; Yugang Dong; Chen Liu; Xin He (BMC, 2024)
Abstract Background The association between urbanization and myocardial infarction in China was not fully understood. We aim to evaluate the association between urbanization level and the risk of myocardial infarction. Methods Participants' data from China Health and Nutrition Survey were analyzed. The survey is an ongoing open cohort with a multistage, random cluster process to draw a sample of over 30,000 individuals in 15 provinces and municipal cities. A multi-component score, urbanization index, was used to measure urbanization level. Urbanization index was categorized by cut-off values of 40, 60, and 80. Baseline characteristics were presented as percentage for categorical variables, and mean or median for continuous variables depending on normality. The association of urbanization index and myocardial infarction risk was evaluated longitudinally by a multilevel mixed-effects parametric survival model with urbanization index as a time-dependent variable using Stata software. Results A total of 16,565 participants without previous myocardial infarction were involved in the cohort. At baseline, urbanization index was positively correlated with myocardial infarction risk factors, including blood pressure, body mass index, diabetes, and stroke. In the univariate model, urbanization index was associated with risk of myocardial infarction in a "U-shape" manner, with the lowest myocardial infarction risk in urbanization index ranging from 40 to 60 (Hazard Ratio 0.55 and p = 0.013). However, in the multivariate model adjusting for myocardial infarction risk factors and other confounders, urbanization index ≥ 40 was consistently associated with lower MI risks (Hazard Ratio 0.46 and p = 0.002 for urbanization index 40-60; Hazard Ratio 0.56 and p = 0.021 for urbanization index 60-80; and Hazard Ratio 0.44 and p = 0.002 for urbanization index ≥ 80). Conclusions Our study indicated that urbanization of living communities was associated with a reduced risk of myocardial infarction.